Covalent immobilization of metal–organic frameworks onto the surface of nylon—a new approach to the functionalization and coloration of textiles - Yu, Ming (Sci Rep, 2016)
The prevention of refractory organic pollution caused by conventional dyeing and the development of new fabrics with various functions are two issues to be solved urgently in the field of textile fabrication. Here, we report a new environmentally friendly route for the simultaneous coloration and functionalization of textiles by the covalent immobilization of a metal–organic framework, Cr-based MIL-101(Cr), onto the surfaces of nylon fabrics by co-graft polymerization with 2-hydroxyethyl acrylate initiated by γ-ray irradiation. The Cr(III) clusters color the nylon fabric, and the color intensity varies with the MIL-101 content, providing a “green” textile coloration method that is different from conventional dyeing processes. An X-ray diffraction (XRD) analysis shows that the nanoporous structure of the original MIL-101 particles is retained during radiation-induced graft polymerization. Numerous nanopores are introduced onto the surface of the nylon fabric, which demonstrated better sustained-release-of-aroma performance versus pristine nylon fabric in tests. The modified fabrics exhibit laundering durability, with MIL-101 nanoparticles intact on the nylon surface after 30 h of dry cleaning.